Japan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2010)
Although fiscal consolidation has short-term costs, the potential long-term benefits are considerable. Although adjustment is important for securing fiscal sustainability, reforms that raise potential growth could also support consolidation. Simulations show that the external environment also matters, but domestic policies should be the priority to raise medium-term growth. In Japan, public policies can help create an environment for more effective capital formation. For Japan, reforms to stimulate private consumption hold significant promise for boosting growth, and this could be achieved by boosting household disposable income.